HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN BERTAHAN DALAM PERMAINAN TENIS LAPANGAN - Mei Henni Palamea; Fadjri, Mukharrar; Emayanti Anggraeni; Abu Bakar; La Robi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between agility and defensive ability in lawn tennis among physical education students. Modern tennis requires the ability to move quickly and perform efficient changes of direction, particularly in defensive situations. However, empirical studies that specifically examine the relationship between these two variables in the context of university students remain limited. This research employed a quantitative design with a correlational approach. The research sample consisted of 30 students selected using a purposive sampling technique. Data were collected through an agility test (change of direction test) and a lawn tennis defensive ability test. Data analysis was conducted using descriptive statistics and the Pearson correlation test with the assistance of SPSS software at a significance level of 0.05. The results of the study indicate that there is a significant and strong relationship between agility and defensive ability (r = -0.682; p < 0.05). The coefficient of determination of 46.5% indicates that agility makes a substantial contribution to defensive ability in lawn tennis. Thus, the research hypothesis is accepted. In conclusion, agility is an important factor associated with the effectiveness of defensive play. These findings provide practical implications for coaches and sports educators to emphasize agility training in tennis learning and coaching programs in order to optimally improve defensive performance.